Thermal Conductivity and Dynamic Viscosity of Nanofluids: A Review - Wahaizad, Safiei; M. M., Rahman; Kulkarni, R. R.; Md Noor, Ariffin; Zetty Akhtar, Abd Malek (Akademi Baru, 2020)
Thermal conductivity is one of the rheology properties that vital for engineering fluid which indispensable for heat transfer enhancement. For this reason, nanofluid is getting wider attention nowadays due to the presence of nanoparticles in the base fluid can further improve thermal conductivity and dynamic viscosity. These are two important properties for new engineering fluid in providing better cooling and lubricating effects, especially in mechanical and tribology applications. In this paper, specifically, nanofluids thermal conductivity and dynamic viscosity are discussed comprehensively. Both properties’ thermal conductivity and viscosity of nanofluids are improved over the base fluid. Furthermore, these two properties increase when more volume concentrations of nanoparticles are added. In addition, the thermal conductivity also improved with increasing the temperature. From the literature review, the maximum enhancement of thermal conductivity for single nanofluid is recorded 36% of MWCNTs in distilled water. On the other hand, the maximum enhancement of viscosity is recorded 39% of Al2O3 in water-ethylene glycol over base fluid. The hybrid nanofluids that consist of more than one type of nanoparticles exhibit better thermal conductivity where the maximum enhancement is recorded 68% of CuTiO2 in deionized water. For dynamic viscosity measurement, the maximum enhancement of hybrid nanofluids is recorded 168% of MgO-MWCNT in ethylene glycol. Therefore, to sum up, hybrid nanofluids are really promising to enhance heat transfer performance especially for heating and cooling applications. The potential of these nanofluids should be explored extensively to discover its advantages over conventional working fluid.